Exploration of Elementary School Students' Cognitive, Affective and Psychomotor Abilities Through Educaplay Interactive Media - Dwi Novita Sari; Rahimah Embong; Irham Habibi Harahap; Hasanah; Nila Lestari; Diva Friska; Indah Sekar Wangi; Siti Asnik Kumala Sari; Yulia Anjani (Postgraduate, University of Mataram, 2025)
Objective: This study discusses the use of the Educaplay interactive platform on students' cognitive, affective and psychomotor abilities in learning about flat shapes in grade V elementary school. Through a comparative analysis of the pre-test and post-test results, it can be seen that Educaplay is able to improve students' cognitive abilities from 60 to 86.67%. As well as affective abilities of 81.84 to 88.08% and Psychomotor Abilities of 80.94 to 85.17%, respectively. In addition, Educaplay also succeeded in providing student involvement during the learning process, so that the learning process became more interactive and interesting. Educaplay provides a more diverse learning experience and makes it easier for students to understand the concept of flat shapes more deeply. The research findings show that the application of Educaplay technology-based media in the learning process has a positive effect on students' cognitive, affective, psychomotor abilities and improves the quality of teaching at the elementary school level. The research findings recommend the use of Educaplay as a learning tool to improve students' cognitive, affective and psychomotor abilities.